Há lugar para o patrimônio cultural na cidade neoliberal? O caso dos imóveis protegidos do centro histórico do Rio de Janeiro - Carlos, Claudio Lima (Technical and Scientific Journal Green Cities, 2025)
Objective – To analyze the contradictions and difficulties faced by urban conservation in Western cities considering the current neoliberal context that has been directly reflected in their governance. The proposed analysis aims to establish possibilities and alternatives that enable the conservation of traditional fabrics, highlighting the case of the city of Rio de Janeiro and the changes suffered in its management, from 1993 onwards.Methodology – In theoretical-methodological terms, it adopts, initially, the historical-critical analysis of the transformations that occurred in European cities from the second half of the nineteenth century onwards, which enabled the broadening of the perception of cultural heritage that began to contemplate, in addition to monuments, sets and traditional urban fabrics. In the face of drastic transformations, urban renewal operations (liberal and post-liberal cities) and massive destruction caused by the two world wars, the conservation of urban environmental diversity became part of the list of concerns of Western planners in the twentieth century with a view to maintaining the cultural identity of cities, despite representing an opposition to capitalist logic,  especially in its current neoliberal stage. The proposed analysis is supported by the thoughts of theorists related to the theme, the contents of letters and international recommendations, among others. In the second stage of the work, the European context is rebounded to the reality of Latin America and, especially, of Brazil, choosing as a case study the planning of the city of Rio de Janeiro, which, from the 1980s onwards, began to have its first specific instrument of urban protection, after decades of policies based on renovation and modernization operations of the city. Initially called Environmental Protection Area (APA), the instrument was later consecrated as a Cultural Environment Protection Area (APAC), by the city's first Decennial Master Plan (1992), prepared after the country's redemocratization. APAC was the first urban instrument of urban protection in the city and created a counterpoint to Rio's urban policy, characterized by permissive legislation that induced unlimited renewal and verticalization. In the 1980s, the legal protection of the city's remaining traditional urban fabrics took place, especially in its historic center. However, from 1993 onwards, neoliberal policies for the management of the city's land were adopted, which were materialized in the abandonment of the Decennial Master Plan (1992) in favor of strategic plans, considered more "friendly" and "flexible" to the interests of the market. In this way, the urban impacts generated - especially in the protected areas of its historic center - by the changes that occurred in the city's governance are evaluated. Finally, the latest conservation initiatives undertaken by the city government in the port area (Porto Maravilha) and in the city center (Reviver Centro) are critically and briefly evaluated, proposing alternatives for a better management of Rio's urban heritage that involves the participation and monitoring of resident and user populations, translating their interests and desires.Originality/Relevance – To contribute to the preservation of the environmental diversity of the city of Rio de Janeiro, which gives rise to several historical layers related to its process of urban occupation.Results – To point out ways for a more democratic management of protected areas and improve the results obtained so far.Theoretical/Methodological Contributions – It is observed that a large part of the theoretical production on urban conservation in Brazilian cities - especially in Rio de Janeiro - gives little or no emphasis to the origins of the political contradictions caused by the practice of urban conservation, highlighting only the consequences of the adoption of successive neoliberal governances that prioritized surplus value and resulted in the growing loss of integrity and authenticity of the protected architectural collection. Thus, it seeks to point out the contradictions and failures of the conservation of urban heritage, seeking to identify its origins, conflicts and real intentions of the State - its main agent - translated by the policies established for this purpose.Social and Environmental Contributions – To contribute to the preservation of the environmental diversity of the city of Rio de Janeiro, which gives rise to several historical layers related to its process of urban occupation.
Keywords: Urban Conservation; Urbanism; Cultural Heritage.